A novel biological 'twin-father' temporal paradox of General Relativity in a Gödel universe – Where reproductive biology meets theoretical physics. (March 2018) - Ashrafian, Hutan
Abstract: Several temporal paradoxes exist in physics. These include General Relativity's grandfather and ontological paradoxes and Special Relativity's Langevin–Einstein twin-paradox. General relativity paradoxes can exist due to a Gödel universe that follows Gödel's closed timelike curves solution to Einstein's field equations. A novel biological temporal paradox of General Relativity is proposed based on reproductive biology's phenomenon of heteropaternal fecundation. Herein, dizygotic twins from two different fathers are the result of concomitant fertilization during one menstrual cycle. In this case an Oedipus-like individual exposed to a Gödel closed timelike curve would sire a child during his maternal fertilization cycle. As a consequence of heteropaternal superfecundation, he would father his own dizygotic twin and would therefore generate a new class of autofraternal superfecundation, and by doing so creating a 'twin-father' temporal paradox.